Penentuan Jumlah Tenaga Kerja dengan Menggunakan Simulasi Antrian di Departemen Produksi di PT. Surya Tubal Indonesia - Murti Astuti; Ilyas Mas'udin (Jurnal Teknik Industri, 2002)
In its productionp rocessa, companyis consistedo f variousd epartmentssu pponingo neanother in a good teamwork to build a single unity. Therefore inefiiciency in one of thosedepartmentsw ill affect other departmentsth at in turn will have impact on production outcome.One of thosed epartmentiss producliond epartmentth at is one of the most imponants ectionswhichp laysi mportanrt olei n productions moothness.One of problemsd isturbingt he smoothnesosf flow processin this departmenits theproblemo f long productl ining markedb y considerablwea itingt ime.T his is certainlyi neffectivesince it will not only disturb the production process flow but also decrease the product qualitycausedb y too muchw aitingt ime in the line. Thereforew, e havet o makea n efforti n reducingth eline sizew hile still considert he costj ust in casea n improvemenits made.T o overcometh ismatter,o new ay we couldt akei s utilizinga line simulationb y optimizings ervicefa cilitiesn umber(numbero f laborf orce)w ith minimumc osta ndp roductw aitingt ime.